Chronic heart failure and the frequency of taking nonsteroidal anti-inflammatory drugs: a register-based study on the possible risks - E. I. Tarlovskaya; Yu. V. Mikhailova (Российский кардиологический журнал, 2020)
Aim. To study the frequency of taking nonsteroidal anti-inflammatory drugs (NSAIDs) and possible adverse events in patients with cardiovascular diseases and heart failure (HF) hospitalized in the Heart Failure Therapy Center (Nizhny Novgorod).Material and methods. According to the local register, the study included 336 patients (men — 156 and women — 180, average age — 71 (63; 80)), hospitalized in Heart Failure Therapy Center in Nizhny Novgorod from February 1 to November 1, 2019. Examination and treatment of patients was performed based on current clinical practice guidelines and standards. According to the results of echocardiography, HF with preserved ejection fraction was diagnosed in 70% of patients, HF with mid-range ejection fraction — in 20%, and HF with reduced ejection fraction — in 10%. Based on data on the outpatient NSAIDs taking, all participants were divided into 2 groups: NSAID+ (n=63) and NSAID(n=273).Results. Among hospitalized patients, 18,7% of patients took NSAIDs on an outpatient basis, without a doctor’s prescription, more often non-selective, mainly by mouth, for stopping arthralgia. The frequency of emergency hospitalizations due to acute HF decompensation depending on the NSAIDs taking did not significantly differ. In the NSAID+ group, acute kidney injury was diagnosed 3 times more often and 10 times more often when NSAIDs were taken ≥1 times a week. Anemia was diagnosed more often in the NSAID+ group, when taking NSAIDs ≥1 times a week. In the NSAID+ group, grade 2-4 anemia was significantly more often diagnosed.Conclusion. None of the patients took the recommended NSAIDs with a low cardiovascular risk. Patients taking NSAIDs were more likely to have a history of atrial fibrillation and acute cerebrovascular accident. Patients from the NSAID+ group had the higher incidence of acute kidney injury and anemia.